Navigating Parenthood and Academia: The Impact of Learning Motivation on Student Success - Paul Niño S. Tabigne (Language, Literature and Education: Research Updates Vol. 1, 2025)
Student parents face unique challenges in balancing academic responsibilities with childcare, financial constraints, and societal expectations. This study explores the multifaceted nature of learning motivation among student parents and highlights the critical role of tailored institutional support in addressing their unique challenges. The study surveyed 101 student parents using a descriptive-correlational design with proportionate stratified random sampling. Data was analyzed through frequency, percentages, mean, standard deviation, t-test, one-way ANOVA, Duncan test for post hoc comparison, and Pearson correlation. Findings revealed that the majority of student parents were aged 18-24, predominantly female, mostly cohabiting with a partner, had a first child aged 0-4, came from low-income families, and had parents who attended college. The respondents exhibited exceptionally high learning motivation, with most achieving superior academic performance. However, the study found no significant differences in learning motivation based on sex, first child’s age, parents’ monthly income, or parental education level. Marital status was the only factor found to significantly influence learning motivation. Furthermore, the study suggests that while learning motivation is high, it may not strongly impact academic performance. To enhance student parents’ educational success, collaborative efforts among policymakers, school administrators, and instructors are recommended to implement inclusive support strategies. This study contributes to educational policy and student support services by emphasizing the importance of institutional interventions tailored to student parents’ needs. Additionally, it underscores the relevance of psychological well-being in academic success. Future research should explore the longitudinal effects of motivation on academic outcomes and examine additional factors influencing student parents’ educational attainment.